Associations of serum multivitamin levels with the risk of non-alcoholic fatty liver disease: A population-based cross-sectional study in U.S. adults - Peng, Hongye; Wang, Miyuan; Pan, Liang; Cao, Zhengmin; Yao, Ziang; Chen, Qiuye; Li, Yanbo; Wang, Yuhua; Lv, Wenliang (Frontiers in Nutrition, 2022)
Vitamins were closely associated with non-alcoholic fatty liver disease (NAFLD) development, but no study had explored the association of serum multivitamin levels with NAFLD risk. We assessed the association between serum levels of both single-vitamin and multivitamins (VA, VB6, VB9, VB12, VC, VD and VE) and the risk of NAFLD, using the database of National Health and Nutrition Examination Survey (NHANES) (cycles 2003-2004 and 2005-2006). We employed multivariable logistic regression and weighted quantile sum (WQS) regression models to explore the association of serum multivitamin levels with NAFLD. Among all 2,294 participants, 969 participants with NAFLD were more likely to be male, older, less educated, or have hypertension/high cholesterol/diabetes. After adjustment of covariates, serum VC/VD/VB6/VB9 levels were negatively correlated with NAFLD risk, while serum VA/VE levels were positively correlated with NAFLD risk. In the WQS model, elevated serum VA/VE levels and lowered serum VC/VD/VB6 levels were linearly associated with increased NAFLD risk. There was a nonlinear relationship between serum VB9/VB12 levels and NAFLD risk. There were evident associations between serum multivitamin levels and reduced NAFLD risk, which was mainly driven by VD/VB9/VC. In conclusion, our findings suggested that serum multivitamin levels were significantly associated with the risk of NAFLD.